Pengenalan E-Fin dan Manfaatnya Pada Guru-Guru SMA Swasta Mulia Medan - Haervi Yunira; Masyitah, Emi; Larasati, Dinda (Publikasi Pengabdian Masyarakat, 2022)
One of the largest sources of income for the state is taxes. In 2015 to 2019, tax contributions accounted for 70-80% of total state revenue from the non-oil and gas sector. In an effort to anticipate the development of information and technology, the Directorate General of Taxes seeks to fulfill the aspirations of taxpayers through E-filling, namely the procedure for reporting SPT, both mass SPT and annual SPT online. Digital taxation activities can now be done online, which previously required E-Fin to do this. E-fin is required to create an account in conducting online tax activities. in the form of an identification number. Ignorance of taxpayers on E-Fin, benefits and how to get it so that if you don't have an E-FIN then the taxpayer can't do tax activities online.